GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

It is currently 04 Aug 2020, 03:31

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

Let d > c > b > a. If c is twice as far from a as it is from d, and b

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 65785
Let d > c > b > a. If c is twice as far from a as it is from d, and b  [#permalink]

Show Tags

New post 11 Nov 2019, 01:43
3
1
18
00:00
A
B
C
D
E

Difficulty:

  55% (hard)

Question Stats:

67% (02:55) correct 33% (02:49) wrong based on 180 sessions

HideShow timer Statistics

GMAT Tutor
User avatar
S
Joined: 16 Sep 2014
Posts: 554
Location: United States
GMAT 1: 780 Q51 V45
GRE 1: Q170 V167
Let d > c > b > a. If c is twice as far from a as it is from d, and b  [#permalink]

Show Tags

New post 11 Nov 2019, 05:18
1
2
We can label the lengths and turn this into an algebra question. Let A = b - a, B = c - b, C = d - c. Then "c is twice as far from a as it is from d" means A + B is twice the value of C. Then the corresponding equality would be (A+B) = 2C. "b is twice as far from c as it is from a" means 2A = B. We can put everything in terms of A, B = 2A, and 2C = A + B = A + 2A = 3A.
Finally, the fraction is asking what is (B + C) / (A + B + C), we can double everything to make it easier to plug in 2C = 3A.

(2B + 2C) / (2A + 2B + 2C) = (4A + 3A) / (2A + 4A + 3A) = 7 / 9.

Ans: D

Alternatively, we could label the lengths since we only care about ratios. C = 1, A + B = 2. Then knowing b is closer to a, we split A + B into three equal lengths, A is 2/3 and B is 4/3. Next we plug in to get (B + C) / (A + B + C) = 7/3 / (3) = 7/9.

Bunuel wrote:
Let \(d > c > b > a\). If c is twice as far from a as it is from d, and b is twice as far from c as it is from a, then \(\frac{(d - b)}{(d - a) }= ?\)

A. 2/9
B. 1/3
C. 2/3
D. 7/9
E. 3/2


Are You Up For the Challenge: 700 Level Questions

Attachments

number line.png
number line.png [ 7.52 KiB | Viewed 2784 times ]


_________________
Source: We are an NYC based, in-person and online GMAT tutoring and prep company. We are the only GMAT provider in the world to guarantee specific GMAT scores with our flat-fee tutoring packages, or to publish student score increase rates. Our typical new-to-GMAT student score increase rate is 3-9 points per tutoring hour, the fastest in the world. Feel free to reach out!
Intern
Intern
avatar
B
Joined: 19 Aug 2019
Posts: 6
Re: Let d > c > b > a. If c is twice as far from a as it is from d, and b  [#permalink]

Show Tags

New post 25 Nov 2019, 10:07
i did not understand the explanation above, can anyone simplify it or give an alternative method?
Intern
Intern
avatar
B
Joined: 14 Jul 2019
Posts: 34
Premium Member
Re: Let d > c > b > a. If c is twice as far from a as it is from d, and b  [#permalink]

Show Tags

New post 01 Mar 2020, 02:36
harshi17 wrote:
i did not understand the explanation above, can anyone simplify it or give an alternative method?


d-a = ad
d-b = bd

ad = ab + bc + cd
bd = bc + cd

So to get the rate of (bd)/(ac), we have to somehow convert this ratio to a common unit. Let's choose bc.

"c is twice as far from a as it is from d":
ac = 2*cd
ab + bc = 2*cd (1)

"b is twice as far from c as it is from a"
bc = 2*ab
ab = 1/2*bc (2)

Combine (1) and (2) we have bc*(1+1/2) = 2*cd
3/2*bc = 2*cd
cd = 3/4*bc

(d-b)/(d-a) = (bc + cd)/(ab + bc + cd) = (bc +3/4*bc)/(1/2*bc + bc + 3/4*bc) = (1+3/4)/(1/2+1+3/4) = (7/4)/(9/4) = 7/9

IMO D
Intern
Intern
avatar
B
Joined: 03 Dec 2017
Posts: 2
Re: Let d > c > b > a. If c is twice as far from a as it is from d, and b  [#permalink]

Show Tags

New post 17 Jun 2020, 10:39
I found assigning values to each point A,B,C and D to be an easier way to solve the question.

As per the question we know that the AC = 2CD and CB=2AB

Let the value of A = 1 and B = 2, so distance between AB= 2-1 =1.
This gives us CB to be 2 units i.e C=4 (4-2=2).
Similarly, since AC = 3 units CD= 1.5 units
which gives us D=5.5 (4+1.5)

Now, using these values we can solve the equation:
(5.5-2)/(5.5-1) = 3.5/4.5 = 7/9
Target Test Prep Representative
User avatar
V
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 11394
Location: United States (CA)
Re: Let d > c > b > a. If c is twice as far from a as it is from d, and b  [#permalink]

Show Tags

New post 20 Jun 2020, 14:27
1
Bunuel wrote:
Let \(d > c > b > a\). If c is twice as far from a as it is from d, and b is twice as far from c as it is from a, then \(\frac{(d - b)}{(d - a) }= ?\)

A. 2/9
B. 1/3
C. 2/3
D. 7/9
E. 3/2




Solution:

We can let a = 0 and b = 1. So c is 3 (since b is 2 units from c, which is twice as far as it is from a), and d is 4.5 (since c is 3 units from a, which is twice as far as it is from d).

Substituting these values into the expression, we have:

(4.5 - 1)/(4.5 - 0) = 3.5/4.5 = 7/9

Answer: D
_________________

  250 REVIEWS

5-STAR RATED ONLINE GMAT QUANT SELF STUDY COURSE

NOW WITH GMAT VERBAL (BETA)

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

Director
Director
User avatar
D
Joined: 12 Dec 2015
Posts: 548
Re: Let d > c > b > a. If c is twice as far from a as it is from d, and b  [#permalink]

Show Tags

New post 20 Jun 2020, 19:44
Let \(d > c > b > a\). If c is twice as far from a as it is from d, and b is twice as far from c as it is from a, then \(\frac{(d - b)}{(d - a) }= ?\)

A. 2/9
B. 1/3
C. 2/3
D. 7/9 --> correct: a <b<c<d, let's say distance from a to b = 2p. Given "b is twice as far from c as it is from a", so distance from b to c = 2*2p=4p => distance from a to c = distance from a to b + distance from b to c = 2p+4p=6p. Given "c is twice as far from a as it is from d" so distance from c to d = (distance from a to c)/2 =6p/2=3p. \(\frac{(d - b)}{(d - a) }= \frac{ (distance-from-b-to-c + distance-from-c-to-d)}{(distance-from-a-to-b+distance-from-b-to-c+distance-from-c-to-d)} = \frac{ (4p+3p)}{(2p+4p+3p)} = \frac{ 7p}{9p}= \frac{ 7}{9}\)
E. 3/2
GMAT Club Bot
Re: Let d > c > b > a. If c is twice as far from a as it is from d, and b   [#permalink] 20 Jun 2020, 19:44

Let d > c > b > a. If c is twice as far from a as it is from d, and b

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





cron

Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne